Lung Neutrophilia in Myeloperoxidase Deficient Mice during the Course of Acute Pulmonary Inflammation - Kremserova, Silvie; Perecko, Tomas; Soucek, Karel; Klinke, Anna; Baldus, Stephan; Eiserich, Jason P; Kubala, Lukas (Oxidative medicine and cellular longevity, 2016)
Systemic inflammation accompanying diseases such as sepsis affects primarily lungs and induces their failure. This remains the most common cause of sepsis induced mortality. While neutrophils play a key role in pulmonary failure, the mechanisms remain incompletely characterized. We report that myeloperoxidase (MPO), abundant enzyme in neutrophil granules, modulates the course of acute pulmonary inflammatory responses induced by intranasal application of lipopolysaccharide. MPO deficient mice had significantly increased numbers of airway infiltrated neutrophils compared to wild-type mice during the whole course of lung inflammation. This was accompanied by higher levels of RANTES in bronchoalveolar lavage fluid from the MPO deficient mice. Other markers of lung injury and inflammation, which contribute to recruitment of neutrophils into the inflamed lungs, including total protein and other selected proinflammatory cytokines did not significantly differ in bronchoalveolar lavage fluid from the wild-type and the MPO deficient mice. Interestingly, MPO deficient neutrophils revealed a decreased rate of cell death characterized by phosphatidylserine surface expression. Collectively, the importance of MPO in regulation of pulmonary inflammation, independent of its putative microbicidal functions, can be potentially linked to MPO ability to modulate the life span of neutrophils and to affect accumulation of chemotactic factors at the inflammatory site.
Keywords: Animals; Peroxidase; Acute Disease; Pneumonia; lipopolysacharidy; pneumonie; Metabolism, Inborn Errors; Mice, Knockout; myši knockoutované; Mice; Lipopolysaccharides; myši; Leukocyte Disorders; poruchy leukocytů; Male; Neutrophils; neutrofily; akutní nemoc; zvířata; mužské pohlaví; Acute Lung Injury; Mice, Inbred C57BL; vrozené poruchy metabolismu; akutní poškození plic; peroxidasa; myši inbrední C57BL